Cognitive behavioral psychopharmacology the clinical practice of evidence-based biopsychosocial integration - Muse, Mark (John Wiley & Sons, Inc., 2018)
"Outlines a comprehensive, evidence-based approach to coordinating psychopharmacological and psychotherapeutic treatments. Cognitive Behavioral Psychopharmacology takes an evidence-based approach to demonstrating the advantages of biopsychosocial integration in interventions for the major psychiatric diagnoses. It is the first and only book to translate the current evidence for cognitive behavioral, psychosocial, and pharmacologic approaches to mental health disorders into clear guidance for clinical practice. There is a burgeoning movement in mental health to acknowledge the entire person functioning across physical, psychological and social spheres, and to integrate medical as well as psychological and social interventions to address the entire spectrum of presenting problems. This book bridges a gap in the professional mental health literature on the subject of standalone versus combined treatment approaches. It reviews the current state of integrative care, and makes a strong case that optimal outcomes are best achieved by an awareness of how and why the cognitive-behavioral aspects of prescribed medical and psychological interventions influence treatment. Each disorder-specific chapter is authored by a prescriber and psychotherapist team who consider all the evidence around treatments and combinations, providing outcome conclusions and concise tables of recommended front-line interventions. Provides a biopsychsocial perspective that integrates the medical, psychotherapeutic, family, and community aspects of the therapeutic process Brings together and compares the current evidence for and against treatments that combine psychopharmacology and cognitive behavioral psychotherapy for major psychiatric diagnoses. Outlines an evidence-based approach to determining which combination of treatments is most appropriate for each of the major psychiatric diagnoses. Describes, in a way that is accessible to both prescribers and therapists, when and how cognitive behavioral therapy can be integrated into pharmacotherapy. The book will appeal to a wide range of mental health professionals, including psychologists, psychiatrists, clinical social workers, licensed professional counselors, marriage and family therapists, and addictions counselors. It also will be of interest to primary care physicians and nurse practitioners who work side by side with mental health professionals"-- Provided by publisher.